Magnetic structure of FexCu100-x magnetoresistive alloys produced by mechanical alloying - Socolovsky, Leandro Martín (2001)
FexCul00-x magnetoresistive alloys were produced by mechanical alloying. X-ray diffraction shows fcc structure. The room-temperature Mössbauer spectra evolves from an asymmetrical doublet below x = 25%, to a broad magnetic hyperfine field distribution above this concentration. Quadrupole splitting of the doublet varies between 0.48 and 0.57 mm/s, and its isomer shift from 0.16 to 0.29 mm/s. Low-temperature Mössbauer spectroscopy displays a Bhf distribution. Magnetization measurements display different features depending on concentration, from mictomagnetism to ferromagnetism. Low-temperature magnetoresistance is measured. Samples with x ∼ 20% exhibit larger magnetoresistivity ratios. Bulk and hyperfine magnetic properties are correlated in order to explain magnetoresistivity features of these samples.